Nuclear signaling pathways and targeting transcription in cancer - Kumar, Rakesh (Cancer Drug Discovery and Development, 2014)
This book presents the most up-to-date information in the area of targeted therapeutics with a particular focus on pathway-centered approaches and transcription by leading authorities in molecular cancer research. The goal is to cover several critical principles of cancer therapeutics, ranging from regulation of cancer associated genes by coregulators, cancer cell signaling, modifiers of epigenome functionality and specific protein domains, and emerging significance of splicing. The book is directed for basic and translational scientists, clinicians, clinical investigators, fellows, residents, graduate students, and educators in the areas of molecular therapeutics and cancer medicine, and medical sciences at-large. Readers will be able to grasp the overall importance of the pathway, associated pathobiology and clinical manifestation, and possible points of intervention with a goal to solidify new cancer therapeutic targets.